Attribution theories in Human Resource Management research: a review and research agenda. Issue 1 (2nd January 2018) - Hewett, Rebecca; Shantz, Amanda; Mundy, Julia; Alfes, Kerstin
Abstract: There is no doubt that attribution theories have made their mark in social psychology and other related disciplines, but their application and extension to the field of HRs is in its infancy. Indeed, HR scholars have recently realized that understanding the process by which individuals explain the causes of behaviors and events provides insight into a host of HR-related issues. In our review of 65 papers, we identified three research streams with different foci – those that focused on HR system strength, on attributions that influence judgements and behaviors within functional HRM domains, and on the attributions employees make of the intent of HR practices. Notably, despite shared foundations, these three streams of literature rarely overlap. We summarize and provide theoretical and empirical directions for future research within each research area to help steer courses in these areas. Importantly, we also draw connections among the three streams to inspire future research to stretch the bounds of current theorizing on attributions in the field of HR.